Maternal Role in Guiding Social Communication to Autistic Children as a Quality of Life Determinant - Utami, Tri; Joebagio, Hermanu; Adriani, Rita Benya (Journal of Maternal and Child Health, 2018)
Background: Autism spectrum disorder is a type of neural development disorder. It is characterized by deficit in social communication, social interaction, and repetitive behavior pattern. It is assumed that maternal role in child education is more dominant than paternal role, because children are closer to their mothers since birth. It is also assumed that the quality of life of autistic children would improve if there is improvement in their social communication and social interaction. This study aimed to examine the maternal role in guiding social communication to autistic children as a determinant of child quality of life. Subjects and Method: This was a qualitative study conducted in public special school in Tangerang District, West Java, from October to December 2017. Informants for this study included 5 mothers of autistic children and 3 teachers-therapists at the public special school. The constructs under study included maternal role in guiding social communication and social interaction in autistic children. The data were collected by in-depth interview, observation, and document review. The data were analyzed by Miles and Huberman method. Results: Mothers had an important role in observing various child behaviors, seeking advice from expert, determining child development need, exploring child sensory-dietary-medical need at home. Other maternal roles included admitting children to primary school or special school that was suitable for child potential development and involving children in simple daily activities at home. The maternal role in guiding social communication was considerably good including communication therapy at home using audio visual aids, stimulating oral motoric skill, providing social interaction therapy by story telling, teaching socialization to children by familiarizing them to greet and handshake with others, and letting them to play with other children. The maternal role in improving quality of life was sufficiently good, so that each child was able to develop their communication and interaction skills with variying levels of improvement. Conclusion: Maternal role in guiding social communication in autistic children is sufficiently good although there is a need to improve its implementation in order to gain improved quality of life. It is adviseable for mothers to carry on guiding program at home so as to develop child potentials and to reduce their weak aspects. Keywords: maternal role, guiding, communication, quality of life, autistic children Correspondence: